Unsafe sex practice and its associated factors among regular undergraduate students of Mekelle University, Ethiopia, 2019: a facility based cross-sectional study : unsafe sex practice and its associated factors - Gezae, Kebede Embaye; Gebretsadik , Letekirstos Gebreegziabher; Abebe, Haftom Temesgen; Meles, Hagazi Gebre; Fisseha, Meseret Abay; G/silasse, Assefa Ayalew; Gebremedhin, Eyerusalem Atakilti; Yetbarek, Arsema Samson (Ethiopian Journal of Reproductive Health, 2020)
Background: Unsafe sex is ranked second among the top ten risk factors to health that may lead to Sexually Transmitted Infections (STIs), unplanned pregnancy and/or unsafe abortion. Despite the high burden of unsafe sex practices in Ethiopia, little was known on reasons and associated factors in the study setting in particular. Objective: To examine unsafe sex practice and its associated factors among regular undergraduate students of Mekelle University, Ethiopia, 2019. Methods: a facility based cross-sectional study design was conducted among randomly selected 797 regular under graduate students of Mekelle University using the multistage sampling design. A multiple logit model was fitted to identify factors associated with unsafe sex practice. Finally, Adjusted Odds Ratio (AOR) was estimated and 95% confidence intervals (CI) were used for statistical decision. Main findings: Overall, approximately 44% of the participants who had sex in the last 12 months practiced unsafe sex. Major reasons to have had unsafe sex were - for fun, lack of awareness, trusting sexual partners and no access to use condom. Dormitory living condition (AOR = 0.44; 95% CI: 0.20 – 0.99) and taking course on Sexual and Reproductive Health (SRH) (AOR =0.49; 95% CI: 0.28 – 0.85) had protective effect against unsafe sex practice. Conclusion: The unsafe sex practice was significantly high in the current study. Thus, comprehensive information and education on SRH has to be implemented by the University to prevent unsafe sex practices associated bad consequences among the students.